Influence of Rare Earth Doping on the Structural and Catalytic Properties of Nanostructured Tin Oxide - Maciel Adeilton; Leite Edson; Probst LuizFD; Carreño NeftalíLV; Nunes Michael; Valentini Antoninho; Fajardo Humberto; Longo Elson (Nanoscale Research Letters, 2008)
Abstract Nanoparticles of tin oxide, doped with Ce and Y, were prepared using the polymeric precursor method. The structural variations of the tin oxide nanoparticles were characterized by means of nitrogen physisorption, carbon dioxide chemisorption, X-ray diffraction, and X-ray photoelectron spectroscopy. The synthesized samples, undoped and doped with the rare earths, were used to promote the ethanol steam reforming reaction. The SnO2-based nanoparticles were shown to be active catalysts for the ethanol steam reforming. The surface properties, such as surface area, basicity/base strength distribution, and catalytic activity/selectivity, were influenced by the rare earth doping of SnO2and also by the annealing temperatures. Doping led to chemical and micro-structural variations at the surface of the SnO2particles. Changes in the catalytic properties of the samples, such as selectivity toward ethylene, may be ascribed to different dopings and annealing temperatures.